2017
DOI: 10.3390/atmos8100187
|View full text |Cite
|
Sign up to set email alerts
|

The Variability of Ozone Sensitivity to Anthropogenic Emissions with Biogenic Emissions Modeled by MEGAN and BEIS3

Abstract: Abstract:In this study, we examined how modeled ozone concentrations respond to changes in anthropogenic emissions when different modeled emissions of biogenic volatile organic compounds (BVOCs) are used. With biogenic emissions estimated by the Model of Emissions of Gases and Aerosols from Nature (MEGAN) and the Biogenic Emissions Inventory System Version 3 (BEIS3), the Community Multi-scale Air Quality with the High-order Direct Decouple Method (CMAQ-HDDM) simulations were conducted to acquire sensitivity co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…BVOCs play crucial roles in both formation and removal processes of ozone (Calfapietra 35 et al, 2013). Comparison between MEGAN and another widely used biogenic emission model, the Biogenic Emission Inventory System (BEIS) indicated that the influence of biogenic emission models on ozone simulation results is among the highest over all the model inputs (Kim et al, 2017;Zhang et al, 2017). The potential influence of biogenic emissions on aerosol modelling results is more complicated.…”
Section: Estimated Isoprene and Monoterpenes Emissions In France Basementioning
confidence: 99%
“…BVOCs play crucial roles in both formation and removal processes of ozone (Calfapietra 35 et al, 2013). Comparison between MEGAN and another widely used biogenic emission model, the Biogenic Emission Inventory System (BEIS) indicated that the influence of biogenic emission models on ozone simulation results is among the highest over all the model inputs (Kim et al, 2017;Zhang et al, 2017). The potential influence of biogenic emissions on aerosol modelling results is more complicated.…”
Section: Estimated Isoprene and Monoterpenes Emissions In France Basementioning
confidence: 99%
“…In particular compounds with very high OH‐reactivities can determine air chemistry in specific periods. The ability of emitting such reactive compounds, however, is very differently expressed in different agricultural species, but this species‐dependence is generally not differentiated in regional air chemistry calculations (Chatani et al., 2015; Kim et al., 2017; Poupkou et al., 2009). For example, significant emissions of limonene, DMNT and sesquiterpenes have been found solely in maize, while in ryegrass only small amounts of isoprene were emitted, rendering this species as low‐impact to air chemistry despite its relatively large emissions of other oxygenated compounds.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that BVOC emissions were estimated using less accurate representations of vegetation types and their BVOC EFs. It is critical to ensure more accurate representation of BVOC emissions within air quality simulations, as this could alter regimes of ambient ozone formation and the relative importance of controls on anthropogenic NO X and VOC emissions [36,37]. However, better representation of BVOC emissions in Japan is not a single solution for eliminating overestimation of its ambient ozone concentrations, as these are greatly influenced by ozone transport from the continent, particularly during summer 2013 [38].…”
Section: Discussionmentioning
confidence: 99%